2007
DOI: 10.1177/1545968307300697
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Blinded, Randomized Crossover Study of Gait Rehabilitation in Stroke Patients Using the Lokomat Gait Orthosis

Abstract: Objective. Treadmill training with partial body weight support has been suggested as a useful strategy for gait rehabilitation after stroke. This prospective, blinded, randomized controlled study of gait retraining tested the feasibility and potential efficacy of using an electromechanical-driven gait orthosis (Lokomat) for treadmill training. Methods. Sixteen stroke patients, mostly within 3 months after onset, were randomized into 2 treatment groups, ABA or BAB (A = 3 weeks of Lokomat training, B = 3 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
245
2
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(263 citation statements)
references
References 40 publications
7
245
2
8
Order By: Relevance
“…Particularly in the field of gait rehabilitation, the effectiveness of robot-assisted intervention is not yet fully realized. The Lokomat gait orthosis provides the advantage of reducing the burden on clinical staff during weight-supported gait training and has been found by some researchers to have advantages over conventional therapies [50][51]. By addressing important psychological aspects of mental engagement in technology-assisted therapies, innovations may be made that help bridge the gap found by some researchers with conventional therapies [52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the field of gait rehabilitation, the effectiveness of robot-assisted intervention is not yet fully realized. The Lokomat gait orthosis provides the advantage of reducing the burden on clinical staff during weight-supported gait training and has been found by some researchers to have advantages over conventional therapies [50][51]. By addressing important psychological aspects of mental engagement in technology-assisted therapies, innovations may be made that help bridge the gap found by some researchers with conventional therapies [52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 presents the summary of 11 randomized controlled trials that compared the effects of exoskeleton robot-assisted gait training with conventional gait training on motor recovery, gait function, and balance in hemiparetic stroke. Mayr et al [10] and Husemann et al [11] reported greater augmented effects from combined exoskeleton robot-assisted gait training combined with conventional gait training compared with conventional gait training alone in 10 subacute stroke patients. Hornby et al [12] conducted a randomized controlled study that compared the effects of exoskeleton robot-assisted gait training and manual facilitation using an assistas-needed paradigm on gait function in patients with chronic stroke.…”
Section: End-effector Type Of Robot-assisted Gait Trainingmentioning
confidence: 99%
“…Similarly, Hornby et al [12] found that Lokomat robot-assisted therapy in 62 patients with chronic stroke was not superior to the conventional gait training. Such inconsistent results in the Lokomat robot-assisted studies may result from different experimental design and testing methods utilized [10], lack of volitional neuromuscular control [14], restricted pelvic and trunk movement control [15,16], arm swing, as well as altered acceleration and deceleration from pre-swing to initial contact [17]. …”
Section: End-effector Type Of Robot-assisted Gait Trainingmentioning
confidence: 99%
“…About them, a lot of intervention effects are reported [1][2][3]. A systematic review of electromechanical assisted gait training using robotic devices was effective at improving the gait ability after stroke [4].…”
Section: Introductionmentioning
confidence: 99%